Creating a Speech Choir: The Bounty of Authentic Audience Experience for Students - Susan Redding Emel (Central States Communication Association, 2018)
For most students at my university, classroom experience alone was the choice for formally developing speaking skills. My idea was to provide students with recurring authentic audience experience, attending to the audience dimension outlined by Derryberry (1989) as a critical requirement of public speaking pedagogy. Through research, a new idea was proposed: Create a Speech Choir, combining talents of the students in one performance. Though it has elements of forensics, reader's theater, choral reading, public speaking and more, it is not identical to any of these. As the team evolved, more pedagogical elements were added including service learning, attention to feedback intervention, and limited social activism in an atmosphere of collaboration and creativity. Quite unexpectedly, however, Speech Choir managed to attract both students with performance confidence and those professing high communication apprehension.